Pembagian Warisan Berdasarkan Sistem Bilateral Perspektif Ulama’ Kontemporer - Ahmad Ainur Bustomy; Zainal (Al-Qadlaya : Jurnal Hukum Keluarga Islam, 2023)
This research aims to analyze the concept of inheritance division based on the bilateral system found in customary law and the opinions of contemporary ulama'. This research method uses a normative juridical approach. Most of the primary data is collected from library materials which contain the latest and most up-to-date scientific knowledge or new understandings about known facts, as well as ideas (ideas) so studies include the Al-Qur'an, Contemporary Ulama's Opinions, and Journals that discuss regarding inheritance based on the bilateral system. The stages of data analysis are Editing, Classifying, Verifying, Analyzing, and Concluding. So that the research data can be accounted for as scientific research, the types of validity of the data in the research include credibility and dependability tests. The results of the research can be concluded that the distribution of inheritance based on a bilateral system is an inheritance system that places more emphasis on equal distribution of inheritance between men and women, also In the distribution of bilateral inheritance, the concept of 1:1 is prioritized, which in its distribution can eliminate injustice compared to the 2:1 concept. The opinion of Contemporary Ulama', as long as the heirs agree, considering that in this modern era there is a change in the position of women, then the concept of 1:1 (bilateral) which is fairer to use can be justified because many women in this modern era have a role like a men became the backbone of the family, in contrast to women in classical times.